The contribution of personality traits and academic and social adjustment to life satisfaction and depression in college freshmen - Smojver-Ažić, Sanja (Psihološka obzorja (Ljubljana), 2010)
The aim of this study is to investigate the role of personality traits and student academic and social college adjustment to their overall life satisfaction and depression. Sample of 492 freshmen completed a battery of measures. Hierarchical regression analyses are applied to analyze the contribution of predictor variables on life satisfaction and depression in the group of male and female students. After controlling for the personality traits, college adjustment had a significant contribution to student depression and life satisfaction. Optimism has a significant protective role only with male, but not with female students.
Keywords: zadovoljstvo z življenjem; depresija; optimizem; prilagojenost; student; študenti; osebnost; personality